The effect of school lockdown on well-being and self-esteem of adolescents during the COVID-19 pandemic in Hungary - Major, David; Falus, Márton; Árva, Dorottya; Eorsi, Daniel; Terebessy, András; Tabak, Adam G.; Fazekas-Pongor, Vince (Frontiers in Public Health, 2024)
Introduction The COVID-19 pandemic affected adolescents’ mental health diversely. Methods Our objective was to examine the one-year change in well-being (WHO-5 well-being index) and self-esteem (Rosenberg self-esteem scale) among secondary school students affected by school lockdown (lockdown group) compared to control students unaffected by the pandemic (pre-pandemic group), utilizing data from a longitudinal survey study conducted in Hungary. We used linear mixed models stratified by sex and adjusted for family structure and family communication. Results Two hundred twenty seven pre-pandemic (128 girls, 99 boys) and 240 lockdown (118 girls, 122 boys) students were included. Both boys’ and girls’ well-being declined in the pre-pandemic group but remained stable in the lockdown group. Post-hoc analyses on WHO-5 items revealed that the pre-pandemic and lockdown groups differed significantly on Item 4 (waking up feeling fresh and relaxed). Boys’ self-esteem did not change over the observation period in neither groups. As for girls, self-esteem of girls during lockdown increased over the observation period, while it did not change in the pre-pandemic group. Better family communication was consistently associated with higher well-being and self-esteem scores for both sexes. Discussion Our results suggested that students may have benefitted from altered academic circumstances due to lockdown (e.g., more sleep) and students struggling with waking up early benefitted the most from lockdown (as shown in our post hoc analysis). Additionally, our results also indicate that families should be involved in mental health promotion interventions, especially in time of adversities. This study underscores the multifaceted effects of pandemic-related factors on adolescent mental health and highlights the need to also investigate the unexpected benefits of pandemic-related restrictions to incorporate this knowledge in health promotion programs targeting the well-being of students.